Linking Job Satisfaction, Motivator-Hygiene Factors, and Loyalty of Online Drivers in Semarang City - Ferdiansah, Riky; Fajri, Annisa (JMK (Jurnal Manajemen dan Kewirausahaan), 2025)
This study aims to analyze the influence of motivational and hygiene factors on the loyalty online bike-taxi driver-partners in Semarang City, with job satisfaction as the mediating variable. A quantitative approach was used by distributing a questionnaire directly and through WhatsApp groups to active driver-partners communities (Grab, Gojek, and Maxim) during June 2025. Data were analyzed using Partial Least Squares and Bootstrapping (SmartPLS4) methods. The result show that hygiene factors have a significant impact on loyalty, both directly and indirectly through job satisfaction. Conversely, motivational factors only have an impact on job satisfaction but do not significantly influence partner loyalty. These findings confirm that job satisfaction is an important mechanism in building loyalty, particularly through managing external business factors such as policy clarity, compensation, and job security. The practical implications of these findings provide insight for digital platform managers to improve partner retention through a more fair and transparent approach based on business needs.